Berlindung dalam Hak Asasi Manusia: Strategi Pekerja Seks di Eropa untuk Mentransformasi Kebijakan Prostitusi - Rima Nusantriani Banurea (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2013)
In European sex worker perspective, prostitution policy in European Countries restrict the nature right of sex workers. Therefore, sex workers in Europe initiating a movement to transform the prostitution policy in Europe. In this movement, sex workers using human right issue as s strategy to framing the sex workers’ right. This article will highlight specifically how sex workers using the human right as a frame for their movement instrument that is the declaration of the rights of sex worker, start from that declaration birth through the international sex workers’ conference until it entering the European Parliament.